Acceptance of Teledermatology Among Primary Health Care Workers in Isabela - Bascos, Louella Fatima Ramos (Poltekkes Kemenkes Malang, Campus III Blitar, 2025)
Teledermatology is emerging as a means of delivering healthcare service to remote areas. In the context of the full implementation of the Universal Health Care, dermatological services can be given to those in the primary care facilities. This study explores the acceptance of teledermatology among primary healthcare workers in Isabela, Philippines, focusing on technological, individual, and organizational factors influencing adoption. Guided by the modified Technology Acceptance Model (TAM), the research evaluates constructs such as perceived usefulness, perceived ease of use, attitude, compatibility, facilitators, subjective norms, and habitual use. A structured survey was administered to 87 purposively selected healthcare professionals, including nurses, midwives, doctors, and barangay health workers. Findings reveal that perceived usefulness and attitude significantly influence intention to use. Younger professionals and nurses exhibited higher acceptance levels, whereas gender and years of service were not significant factors. Despite positive perceptions, challenges remain in habitual use, underscoring the need for reliable internet access, administrative support, and ongoing training. The study affirms the relevance of TAM in this context and highlights the importance of targeted interventions to support sustainable teledermatology integration in primary care settings. In conclusion, this study highlights the acceptance of teledermatology among primary health care workers in Isabela.